S-Block carbodicarbene chemistry: C(sp3)–H activation and cyclization mediated by a beryllium center. Issue 13 (25th January 2019) - Walley, Jacob E.; Breiner, Grace; Wang, Guocang; Dickie, Diane A.; Molino, Andrew; Dutton, Jason L.; Wilson, David J. D.; Gilliard, Jr., Robert J.
Abstract : The first examples of carbodicarbene (CDC)-s-block complexes have been synthesized. Unusual C–H bond activation and cyclization discovered. Abstract : The first examples of carbodicarbene (CDC)-s-block complexes have been synthesized. The addition of base or reducing agent to a CDC–beryllium (chloride)(hexamethyldisilazide) adduct results in the unprecedented activation of a pendant C(sp 3 )–H bond and cyclization of the CDC to form a five-membered beryllium metallacycle. This also represents the first example of chemical activation of a CDC which transforms the ligand from monodentate neutral to chelating anionic.